Spirituality in contemporary art: Claudio Parmiggiani - Massimo Recalcati (PsicoArt, 2019)
The text takes up almost literally, except for some inevitable formal changes, the content of the Lectio magistralis held by the author on June 2019 in Reggio Emilia at the church of San Filippo Neri in Reggio Emilia. The article examines the relationship between Claudio Parmiggiani’s work and the dimension of spirituality: “That which is spiritual of Parmiggiani - the author writes - is a spiritual rooted in the immanence of life, in the mystery of life.” In the article several works by the artist are taken into consideration: starting from the High Altar of the Cathedral of Reggio Emilia in 2011 going back to the Delocations of 1970.